ANALISIS KEMAMPUAN BERPIKIR KRITIS MATEMATIK SISWA SMP DI KOTA CIMAHI PADA MATERI SEGIEMPAT DAN SEGITIGA - Andriani, Dewi; Nurjaman, Adi (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
Critical thinking ability is a process to leads to withdrawal conclusion about what do you believed and action will do. The importance of critical thinking ability on education and that is the main purpose of instructional, there are four importance component  for build that ability that is (a) explain and clarify; (b) asking the correct question to clarify or challenge; (c) consider the source of credibility; (d) problem solving and illustrates the conclusion. Method of the research will use is qualitative descriptive. As for the sample in this research is ninth of grade students on Cimahi city from high ability, medium and low. For the instrument test of critical thinking ability will deliver to students are five questions and following with interview for each student. Then, the results obtained was the level of critical thinking ability mathematics students in Cimahi city. Based on the writing test and the results of the interview with the low-level students.